COMPACTION PROPERTIES OF ORGANIC FOAMING WARM MIX ASPHALT - BIN MULIANA, MUHAMMAD FAREEZ (Universiti Teknologi PETRONAS, 2018)
Warm Mix Asphalt (WMA) is a technology than can reduce the compaction and mixing temperature of asphalt binder by reducing the binder’s viscosity. This paper gives a detailed review regarding WMA from past researchers and practical experience from author in terms of compaction properties such as compaction and mixing temperature, air void, Marshall Stability and Flow, bulk density, specific gravity and many others. Moreover, this paper also states the different types of WMA additives, with its setbacks and benefits when using them which is essential for better understanding during application of WMA in pavement constructions. Marshall Mix Method and Testing was performed to analyze the difference in the compaction properties between conventional Hot Mix Asphalt (HMA) and Warm Mix asphalt.